2016
DOI: 10.1016/j.cobeha.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Post-decisional accounts of biases in confidence

Abstract: Most models of decision-making suggest that confidence, the "feeling of knowing" that accompanies our choices, is constructed as the decision unfolds. However, more recent studies have noted that processes occurring after we commit to a particular choice also affect this subjective belief. This leads to following question: when are we better judges of ourselves?If, after a decision, evidence continues to accumulate in an unbiased manner, then our confidence judgements should improve. Conversely, if post-decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 51 publications
8
96
3
Order By: Relevance
“…These results indicate that early motion evidence simultaneously informs both choice and confidence (Zylberberg et al, 2012). They are inconsistent with the proposal that choice and confidence are resolved in strict succession, as these predict that confidence selectivity ought to emerge later than choice-related signals (Pleskac and Busemeyer, 2010; Navajas et al, 2016). …”
Section: Resultscontrasting
confidence: 65%
“…These results indicate that early motion evidence simultaneously informs both choice and confidence (Zylberberg et al, 2012). They are inconsistent with the proposal that choice and confidence are resolved in strict succession, as these predict that confidence selectivity ought to emerge later than choice-related signals (Pleskac and Busemeyer, 2010; Navajas et al, 2016). …”
Section: Resultscontrasting
confidence: 65%
“…2) began with a central fixation point presented for a random duration between 500 and 1000 ms, followed by a grating for 33 ms, followed by fixation again, which dimmed slightly after 600 ms to indicate that responses could be made with no time limit. This 600 ms grace period was included to allow the evoked response in the EEG to unfold without motor contamination and to ensure that subjects had accumulated the same amount of evidence for both the orientation and confidence judgment (Navajas, Bahrami, & Latham, 2016). Note that this precluded the study of reaction times.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that humans often tend to overestimate or underestimate their confidence, ending up in reporting high values of confidence when they made the wrong decision [10], [11]. If this happens, the group decisions made using a decisionsystem based on self-reported confidence are likely to be badly influenced by error-prone group members, leading to poor performance.…”
Section: B Contributionmentioning
confidence: 99%
“…However, it should be noted that there is significant overlap between the box-plots in Figure 4. Also, there is a marked asymmetry in the "incorrect" distribution, caused by the presence of trials with an inverse relation between confidence and correctness (i.e., the overconfident behaviour [10]). Conversely, we see more separation between the distributions in Figure 5, and no significant asymmetry, suggesting that the cBCI's estimates of decision confidence are more robust and accurate predictors of correctness than the self-reported confidence.…”
Section: B Group Performancementioning
confidence: 99%